Determinants of quality education in private universities from student perspectives - Ashraf, Mohammad A.; Osman, Abu Zafar Rashed; Ratan, Sarker Rafij Ahmed (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of the present study is to identify the determinants that potentially influence quality education in private universities in Bangladesh. Design/methodology/approach – To attain this objective, 234 data were collected through face-to-face interviews on campus during February-March 2013 from Bachelor of Business Administration students. The bootstrapping procedure through AMOS was applied to analyze the data apart from exploratory and confirmatory factor analysis.Findings – The bootstrap path coefficients suggest that seven factors are statistically significant among the eight postulated independent variables. The outcomes of the confirmatory factor analysis, such as factor loading's, eigenvalues and percentage of variance explained, as well as reliability coefficients, are observed to conform to the results of path analysis, such as item loading's and path coefficients, which consistently increased the robustness of the study.Practical implications – The overall results of the study would be beneficial to the planners to formulate the proper policy to ensure the quality excellence in the private higher educational institutes. Originality/value – The research is based on empirical evidence which deserves originality in terms of data and methods of analysis